Uranium Mineral Transport in the Peña Blanca Desert: Dissolution or Fragmentation? Simulation in Sediment Column Systems - Victoria Pérez-Reyes; Rocio M. Cabral-Lares; Jesús G. Canche-Tello; Marusia Rentería-Villalobos; Guillermo González-Sánchez; Blanca P. Carmona-Lara; Cristina Hernández-Herrera; Fabián Faudoa-Gómez; Yair Rodríguez-Guerra; Gregorio Vázquez-Olvera; Jorge Carrillo-Flores; Ignacio A. Reyes-Cortés; et al. (Applied Sciences)
The Sierra Peña Blanca (SPB) region in Chihuahua, Mexico contains a significant uranium deposit representing about 40% of the country’s reserves. Common uranium minerals in this area include uranophane, schoepite, and weeksite/boltwoodite, with several superficial occurrences. Mining activities in the 1980s left unprocessed uranium ore exposed to weathering, with potential transport towards Laguna del Cuervo. This study presents an experimental simulation of uranium transport in SPB sediments using three approaches: (i) a batch experiment to evaluate the ideal adsorption of (UO2)2+ by fine sediment; (ii) a column system fed with 569 mgU L−1 UO2(NO3)2 to simulate adsorption by different sediment particle sizes; (iii) a column system with an upper horizon of uranophane from the area, fed with deionized water, to simulate uranium weathering and transport in particulate material, determined by liquid scintillation counting, revealed that the clay fraction had the highest adsorption capacity for U. X-ray Absorption Fine Structure (XAFS) analysis at the U L3 edge confirmed the U(IV) oxidation state and the fittings of the extended XAFS spectra confirmed the presence of the uranophane group of minerals. X-ray tomography further corroborated the distribution of particulate minerals along the column. The results suggest that the primary transport mechanism in SPB involves the fragmentation of uranium minerals, accompanied by eventual dissolution and subsequent adsorption of U onto sediments.